2017
DOI: 10.1016/j.ccell.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Selection of Genomic Alterations Dictates Cancer Evolution and Oncogenic Dependencies

Abstract: Cancer evolves through the emergence and selection of molecular alterations. Cancer genome profiling has revealed that specific events are more or less likely to be co-selected, suggesting that the selection of one event depends on the others. However, the nature of these evolutionary dependencies and their impact remain unclear. Here, we designed SELECT, an algorithmic approach to systematically identify evolutionary dependencies from alteration patterns. By analyzing 6,456 genomes from multiple tumor types, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 78 publications
1
123
0
1
Order By: Relevance
“…Supervised prediction of patient response using CFE interaction Mina et al (2017) The list of CFEs was collected from Mina et al (2017). ANOVA Pvalue < 0.05 was used to filter out non-significant drug and CFE pairs, resulting in 1,444 drug CFE pairs with significant association.…”
Section: Du-sr-based Unsupervised Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…Supervised prediction of patient response using CFE interaction Mina et al (2017) The list of CFEs was collected from Mina et al (2017). ANOVA Pvalue < 0.05 was used to filter out non-significant drug and CFE pairs, resulting in 1,444 drug CFE pairs with significant association.…”
Section: Du-sr-based Unsupervised Predictormentioning
confidence: 99%
“…CFEs) and demonstrated that they could be used to predict drug response of 265 drugs in vitro. Similarly,Mina et al (2017) identified genetic interactions involving these CFEs and demonstrated they predict drug response in cell lines. To systematically evaluate whether these could also determine drug response in patients, we used the occurrence of CFEs and CFE interactions in patients' tumor as features to build supervised models (Materials and Methods) predicting the response for each drug in TCGA.…”
mentioning
confidence: 99%
“…Cancer growth is largely the consequence of multiple, cooperative genomic alterations 13 . Cancer genome sequencing has catalogued many of these alterations; however, the combinatorial effects of these alterations on tumor growth is largely unknown 1,4 .…”
mentioning
confidence: 99%
“…Even the tumor suppressor alterations that conferred advantage in all three contexts ( Rb1 and Apc ) still exhibited context-dependent magnitudes of tumor suppression. Such widespread context dependency is overlooked by global surveys of drivers, where driver interactions are either ignored 1,2 or presumed to be sufficiently rare and/or weak to justify considering only marginal correlations 3,13 . Nonetheless, our fitness measurements generally agree with mutation co-occurrence patterns in human lung cancer, despite the limited statistical resolution of these data (Spearman R = 0.50, P = 0.03, Supplementary Fig.…”
mentioning
confidence: 99%
“…Indeed, the analysis of the mutational landscape of cancer has also uncovered the existence of mutual exclusivity and co-occurrence patterns among driver gene alterations [16,69]. Many computational tools have been developed to identify those combinatorial patterns experimentally (i.e via CRISPR-Cas9 screens [70,71]) or computationally [72][73][74][75][76][77][78][79]. Patterns of mutual exclusivity can arise from functional redundancy, context-specific dependencies (i.e tumor type or sub-type specific driving alterations), or synthetic lethality interactions.…”
Section: Discussionmentioning
confidence: 99%